Theoretical and experimental studies of new modified isoflavonoids as potential inhibitors of topoisomerase I from Plasmodium falciparum. - Wilian A Cortopassi (Public Library of Science (PLoS), 2014)
DNA topoisomerase I from Plasmodium falciparum (PfTopoI), a potential selective target for chemotherapy and drug development against malaria, is used here, together with human Topo I (HssTopoI), for docking, molecular dynamics (MD) studies and experimental assays. Six synthetic isoflavonoid derivatives and the known PfTopoI inhibitors camptothecin and topotecan were evaluated in parallel. Theoretical results suggest that these compounds dock in the binding site of camptothecin and topotecan inside both enzymes and that LQB223 binds selectively in PfTopoI. In vitro tests against P. falciparum blood parasites corroborated the theoretical findings. The selectivity index (SI) of LQB223 ≥ 98 suggests that this molecule is the most promising in the group of compounds tested. In vivo experiments in mice infected with P. berghei showed that LQB223 has an antimalarial activity similar to that of chloroquine.